Analisis Theory Planned Behavior (TPB) terhadap Perilaku Ibu dalam Imunisasi Balita di Kecamatan Tenom Kabupaten Aceh Jaya - Hestia Sari Ernisa; Darmawan Darmawan; Firman Firdaus Saputra; Maiza Duana; Eva Flourentina Kusumawardani (Yayasan Literasi Sains Indonesia, 2025)
Toddler immunization is an important effort to prevent infectious diseases and improve children’s health. However, immunization coverage in Tenom District is still low, at 25.6%. This study aims to analyze toddler immunization behavior based on the Theory Planned Behavior (TPB). The method used is quantitative with a cross-sectional survey design, involving 180 respondents from 18 villages selected by cluster random sampling. Inclusion criteria include mothers with toddlers aged 0-5 years, living in the Teunom health center area, being able to speak Indonesian, not using a caregiver, and willing to be respondents. Data were collected through interviews using questionnaires and direct observation of toddler KIA books. Data analysis using the chi-square test and multiple logistic regression. The results showed that bivariately there was a significant influence between attitude (OR = 2.128; P = 0.017), perceived behavioral control (OR = 2.577; P = 0.003), and intention (OR = 2.652; P = 0.002) on the type of immunization. However, subjective norms had no effect (OR = 1.706; P = 0.094). Multivariately, the intention variable became dominant with OR 2.241 and P = 0.019, indicating that respondents with bad intentions were twice as likely to not receive complete immunization. The conclusion of this study is that there is a relationship between attitude, perceived behavioral control and intention towards the type of immunization in toddlers. While there is no relationship between subjective norms and the type of immunization in toddlers.